SERVANT LEADERSHIP AND ORGANIZATIONAL PERFORMANCE IN THE AVIATION INDUSTRY: A SYSTEMATIC LITERATURE REVIEW - Mirah Berliandari, Ni Komang Putri; Putri, Rany Adiliawijaya; Gomez, Aurelio Jr, S. (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2024)
Servant leadership prioritizes serving others, believing it enhances organizational performance. This review aimed to explore how servant leadership relates to organizational performance in air traffic control centers. This research aimed to conduct a systematic literature review to examine research on the impact of servant leadership on organizational performance, specifically within air traffic control centers. The review included peer-reviewed journals, conference papers, and related reports. The result indicated a positive relationship between servant leadership and organizational performance in air traffic control centers. Servant leaders in this context improved employee satisfaction, enhanced operational efficiency, and fostered a collaborative and innovative culture. Recognizing the importance of servant leadership in air traffic control centers can yield practical benefits by enhancing overall performance and safety outcomes. By embracing servant leadership principles, organizations can cultivate a supportive work environment that promotes employee well-being and operational excellence. In conclusion, this systematic literature review highlighted the critical role of servant leadership in improving organizational performance in air traffic control centers. Future research should delve deeper into the specific mechanisms by which servant leadership influences various aspects of organizational effectiveness.